The Influence of Women's Leadership and Work Culture in Soes on Employee Performance - Afiya Noor Dewi; Eko Sakapurnama (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of women's leadership and work culture on employee performance in the State-Owned Enterprises (SOEs). The issue of gender equality is a major concern in this context, considering that there are still structural and cultural challenges that hinder women's participation in strategic positions. This study uses a quantitative approach with an associative strategy and multiple linear regression method to measure the influence of two independent variables—women's leadership and work culture—on employee performance as dependent variables. Data is collected through the distribution of questionnaires and tested for validity and reliability to guarantee the reliability of the results. The results of the analysis show that both independent variables have a significant influence on improving employee performance. These findings underscore the importance of strengthening an inclusive work culture and supporting women's strategic roles in leadership to drive organizational productivity and effectiveness. The practical implication of this research is the need to strengthen gender-based policies and transform work culture in SOEs to create a more equal and progressive workspace.